Linkages between pelagic and benthic biota in a deteriorated coastal lake after restoration, Maruit, Egypt - Hanan Mitwally; Hoda El Rashidy; Paul Montagna (Environmental Monitoring and Assessment, 2023)
Until the 1960s, Lake Maruit was one of Egypt’s most productive coastal brackish lakes. Continuous polluted discharge from Alexandria city resulted in long-term deterioration. The Egyptian government started a lake restoration program in 2010. Biological linkages between pelagic and benthic communities were assessed in November 2012 using parasitism and predation. This study examined ectoparasites infesting tilapia fish from 300 samples. The platyhelminth ectoparasite, Monogenea, and parasitic-copepod Ergasilus lizae were detected. Platyhelminthes parasitized Oreochromis niloticus and Oreochromis aureus , whereas the crustacean parasitized Coptodon zillii . The parasitic prevalence was low for Cichlidogyrus sp. and Ergasilus lizae . Benthic biotas were similar across basins. Fish abundance does not respond directly to benthic biotic components. Phytoplankton and benthic microalgae were not the main fish diet. Data on Halacaridae and fish clustered, indicating that either Halacaridae responds to their environment like fish or fish prey upon them because of their size. Linear correlations between pelagic, benthic biota, and parasite-infected fish indicate parasites may control their hosts. Some bioindicators indicate that stressed ecosystems differ from unstressed ecosystems. Fish species and biota abundances were low. Inconsistency in the food web and an absence of direct interactions between prey and predators are bioindicators of disturbed ecosystems. The low prevalence of ectoparasites and lack of heterogenous distribution of the various examined biota are bioindicators of habitat rehabilitation. Ongoing biomonitoring to better understand habitat rehabilitation is suggested.

Diversity and ecology of crustaceans from shallow rocky habitats along the Mediterranean coast of Egypt - Rasha Hamdy; Joachim Langeneck; Manal Mohamed Atta; Mohamed Moussa Dorgham; Hoda Hassan El-Rashidy; Luigi Musco (Marine Biodiversity, 2019)

Rare parasitic copepods (Siphonostomatoida: Lernanthropidae) from Egyptian Red Sea fishes - Hoda Hassan El-Rashidy; Geoffrey Allan Boxshall (Systematic Parasitology, 2016)

Parasitic copepods from Egyptian Red Sea fishes: Bomolochidae Claus, 1875 - Hoda Hassan El-Rashidy; Geoffrey Allan Boxshall (Systematic Parasitology, 2016)

A new parasitic copepod (Cyclopoida: Bomolochidae) from a ponyfish (Leiognathidae) caught in Egyptian Mediterranean waters, with a review of hosts and key to species of Nothobomolochus - Hoda Hassan El-Rashidy; Geoffrey Allan Boxshall (Systematic Parasitology, 2014)

A new copepod (Siphonostomatoida: Lernanthropidae) parasitic on a Red Sea immigrant dragonet (Actinopterygii: Callionymidae), with a review of records of parasitic copepods from dragonets - Hoda H. El-Rashidy; Geoff A. Boxshall (Systematic Parasitology, 2012)

The discovery of Caligus temnodontis Brian, 1924 (Copepoda: Caligidae) from the bluefish Pomatomus saltatrix (Linnaeus) in the eastern Mediterranean Sea - Argun A. Özak; Hoda H. El-Rashidy; İbrahim Demirkale; Geoff A. Boxshall (Systematic Parasitology, 2010)

Parasitic copepods on immigrant and native clupeid fishes caught in Egyptian coastal waters off Alexandria - Hoda El-Rashidy; Geoff A. Boxshall (Systematic Parasitology, 2010)

New species and new records of Ergasilus Nordmann (Copepoda: Ergasilidae) from the gills of grey mullet (Mugilidae) - Hoda H. El-Rashidy; Geoff A. Boxshall (Systematic Parasitology, 2002)

Description of a new Nipergasilus species (Family: Ergasilidae) from the gills of grey mullet - Hoda H. El-Rashidy; Geoffrey A. Boxshall (Hydrobiologia, 2000)